Computation in the Analysis of Techno-Economic of the Production of Al2O3 (Aluminum Oxide) Nanoparticles through Precipitation Method - Yusrianti Sabrina Kurniadianti; Adzra Zahra Ziva; Yuni Kartika Suryana; Risti Ragadhita; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2021)
This study aims to demonstrate computation in the techno-economic analysis of the production of aluminum oxide (Al2O3) using the precipitation method on an industrial scale. This evaluation is based on the perspective of technical and economic evaluation. Several economic evaluation parameters were analyzed to obtain potential information from the manufacture of Al2O3 nanoparticles based on gross profit margin, payback period, and cumulative net present value. The results of this study identified that the manufacture of Al2O3 nanoparticles using the precipitation method could be done industrially. Based on the engineering perspective, Al2O3 nanoparticles can be produced as much as 6.9 tons and earn an annual profit of 144,635.69 USD with a period of 20 years. To ensure that this project can be carried out, an economic evaluation is made based on estimates of ideal and non-ideal conditions, including tax increases, sales changes, raw material prices, utility prices, and labor’s salary. This study is expected to provide information for the manufacture of Al2O3 nanoparticles using the precipitation method on an industrial scale.